Treatment of labial frenal attachment and gingival hyperpigmentation in a 17-years-old patient - Irmah Basir; Hasanuddin Thahir (Makassar Dental Journal, 2020)
Objectives: This case report describes the treatment of labial frenal attachment and gingival hyperpigmentation in an adolescent patient who will undergoing orthodontic treatment; the frenulum type is papilla penetrating. The abnormality of this frenulum leads to diastema on anterior region particularly centralis incisor. This frenal attachment appailing the tooth movement and play a role in occurence of relapse, and interfere with the oral hygiene. Case: An adolescent patient came to Department of Periodontic for high frenum referred by her orthodontic. Gingival depigmentation is treated after frenectomy procedure for aesthetic purposes. The healing process goes well and there are no signs of inflammation. Conclusion: Frenectomy and gingival depigmentation were treated withscrapping technique with scalpel. This treatment exhibit a good attachment of frenum and a new formation of gingiva increases a patient confidence.